Essential MATLAB for engineers and scientists - Hahn, Brian D. (Elsevier/Academic Press, 2010)
This text presents MATLAB both as a mathematical tool and a programming language, giving a concise and easy to master introduction to its potential and power. This edition has been updated to include coverage of Symbolic Math and SIMULINK.
Includes index.
Keywords: MATLAB.; Numerical analysis -- Data processing.; elektronické knihy; electronic books